2007
DOI: 10.1007/s10802-007-9109-4
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of the Distinction between Reactive and Proactive Aggression in Children and Adolescents

Abstract: The present meta-analytic review aimed to clarify divergent findings concerning the relation between reactive and proactive aggression in children and adolescents. Fifty-one studies with 17,965 participants were included in the analysis. A significant correlation between reactive and proactive aggression was found. The strength of this relation varied considerably between studies, from −.10 to .89. Observational assessment and tilt/noise tasks were associated with smaller correlations than questionnaires. With… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
121
5
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 234 publications
(145 citation statements)
references
References 71 publications
16
121
5
3
Order By: Relevance
“…Second, most psychological processes were positively correlated to the bully or victim nomination scores—with the exception of happy victimizer emotions, which was related to neither. Third, the correlation between reactive and proactive motives was lower than typically reported in questionnaire studies (i.e., r = .43, compared to r  =.70 as found in a meta‐analysis; Polman et al, 2007). This relatively low correlation enabled us to study distinct motives in bully and bully‐victim groups, beyond these children's shared tendency to aggress.…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…Second, most psychological processes were positively correlated to the bully or victim nomination scores—with the exception of happy victimizer emotions, which was related to neither. Third, the correlation between reactive and proactive motives was lower than typically reported in questionnaire studies (i.e., r = .43, compared to r  =.70 as found in a meta‐analysis; Polman et al, 2007). This relatively low correlation enabled us to study distinct motives in bully and bully‐victim groups, beyond these children's shared tendency to aggress.…”
Section: Resultsmentioning
confidence: 65%
“…As a result, children's motives could have been confounded with their actual aggressive behavior: respondents may have given high ratings to children who frequently hurt others, even though these children did not have the motive to dominate. Illustrative of this confound, such questionnaires typically yield high relations between reactive and proactive motives ( r =  .70 as found in a meta‐analysis; Polman, de Castro, Koops, van Boxtel, & Merk, 2007). To address this issue, the present study used a questionnaire that assesses children's motives independently of their actual aggressive behavior (Polman, de Castro, Thomaes, & van Aken, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Structural equation analyses found higher-order (pure) reactive and (pure) proactive components that were not significantly related. A metaanalysis confirmed that much lower correlations between reactive and proactive aggression are found with measures that separate form and function such as the Little et al (2003b) measure (Polman et al 2007).…”
Section: Methodological Problemsmentioning
confidence: 90%
“…Researchers have suggested that the high correlation between reactive and proactive aggression is due to two methodological problems of the measures being used and is thus not necessarily indicative of a lack of discriminant validity (Card and Little 2006;Little et al 2003a,b;Polman et al 2007;Polman et al 2008, submitted for publication).…”
Section: Methodological Problemsmentioning
confidence: 99%
See 1 more Smart Citation